Peran Budaya Organisasi Dalam Membangun Kualitas Pendidikan - Rokim; Amin Fathih, Muhammad; Khozim Muhlis, Nur (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
Educational institutions are always required to produce quality graduates. Quality education will be achieved through a conducive learning environment. Organizational culture is one of the factors that have a major influence in influencing individual and group aspects that exist in an organizational environment. So that this influence will certainly be great potential in building positive activities for members in the organization so that they are always oriented towards achieving quality. This article aims to examine the theoretical concept of organizational culture in building quality education. The research method used is a literature review with data analysis using content analysis. The study results show that the concept of building a quality culture in educational institutions lies in the scenarios created by leaders in building a positive culture in the institutions they lead. A culture of quality education can be built through the power possessed by a leader, the formulation of a vision, mission, curriculum, rules, and regulations directed to the values of discipline, teamwork, honesty, sincerity and mutual support. Building good communication between leaders and members, training, good ethics, trust and respect is also an important element in building an organizational culture that is oriented toward achieving quality education.